2020
DOI: 10.26434/chemrxiv.13262660.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Styrene Copolymerization of Novel Trisubstituted Ethylenes: 2. Alkoxy Ring-substituted 2-Methoxyethyl Phenylcyanoacrylates

Abstract: <p>Novel trisubstituted ethylenes, alkyl ring-substituted 2-methoxyethyl phenylcyanoacrylates, RPhCH=C(CN)CO<sub>2</sub>CH<sub>2</sub>CH<sub>2</sub>OCH<sub>3</sub><sub> </sub>(where R is 2-methoxy, 3-methoxy, 4-methoxy, 2-ethoxy, 3-ethoxy, 4-ethoxy, 4-propoxy, 4-butoxy, 4-hexyloxy) were prepared and copolymerized with styrene. The ethylenes were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-substituted benzaldehydes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 10.6 and 31.2 mol% of APCA is present in the copolymers prepared at ST/ APCA = 3 (mol), which is indicative of relatively high reactivity of the APCA monomers towards ST radical which is typical of alkoxy ring-substituted APCA [13][14][15][16][17][18][19][20][21][22][23]. Since APCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated APCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Apca Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 10.6 and 31.2 mol% of APCA is present in the copolymers prepared at ST/ APCA = 3 (mol), which is indicative of relatively high reactivity of the APCA monomers towards ST radical which is typical of alkoxy ring-substituted APCA [13][14][15][16][17][18][19][20][21][22][23]. Since APCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated APCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Apca Copolymersmentioning
confidence: 99%
“…Earlier we have reported synthesis and styrene copolymerization of a number of alkoxy ring-substituted methyl [13][14][15], ethyl [16,17], propyl [18], isopropyl [19], butyl [20], isobutyl [21], 2-methoxyethyl [22], and octyl [23] phenylcyanoacrylates.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of a number of alkoxy ring-substituted methoxy [19][20][21], ethyl [22,23], propyl [24], isopropyl [25], butyl [26], isobutyl [27], 2methoxyethyl [28] PCAs.…”
Section: Introductionmentioning
confidence: 99%